Effect of Genistein and Glycitein on production performance, egg quality, antioxidant function, reproductive hormones and related-genes in pre-peak laying hens - Uchechukwu Edna Obianwuna; Xinyu Chang; Rupeng Wu; Jing Wang; Hai-jun Zhang; Shu-geng Wu; Kai Qiu (Poultry Science, 2024)
ABSTRACT: Genistein (GEN) and Glycitein (GLY), are types of isoflavone extracted mainly from soy plants, although GEN is associated with stronger antioxidant and growth-promoting effects. The impact of dietary GEN and GLY on reproductive performance, egg quality, and bone quality were investigated in the study. Additionally, to explore the underlying mechanism of action, the serum hormone levels and reproductive-related genes were investigated. A total of 378 Hy-Line Brown laying hens (120 days old) were randomly allocated to 3 dietary groups (Control), (GLY, and GEN at 50 mg/kg respectively) for a period of 8 wk. Each treatment has 126 birds (7 replicates of 18 birds each). Results were analyzed in 2 phases: wk 1 to 4, and 5 to 8 of feeding trial. The results indicated that supplemental GEN significantly increased egg number, hen-day production (HDP), and egg mass during wk 1 to 4, whereas, both glycitein and genistein increased egg number, egg weight, egg mass, HDP and improved feed-egg-ratio during wk 5 to 8. Egg quality analysis revealed significant improvements in eggshell quality; gloss, thickness, strength, and albumen quality indices (albumen height, Haugh unit, thick albumen fraction) due to dietary treatments. Also, the tibia strength, Ca content in the tibia ash and bone mineral content, were significantly increased by the dietary treatments. Significant increases in the serum levels of E2, LH, FSH, T3, T4, and GH, and the activity of antioxidant enzymes; SOD, CAT, GSH while reducing the level of MDA, was notable with the treatments. Additionally, reproductive-related genes: ESR1, FSHR, PRLR, GNRH1 were significantly upregulated by the supplementation of GEN and GLY. The efficacy of GEN in relation to the evaluated parameters was superior to that of GLY. Conclusively, we speculate that the improvement on laying performance, egg quality and tibia quality may be related to promoting effect of isoflavones on calcium metabolism, antioxidant function, reproductive hormones and related genes. Therefore, supplemental GEN at a dosage level of 50 mg/kg, can be used to promote laying performance, sustain egg production and maintain the physiological function of young laying hens.